2022
DOI: 10.3390/su14042225
|View full text |Cite
|
Sign up to set email alerts
|

Digital Paradox: Platform Economy and High-Quality Economic Development—New Evidence from Provincial Panel Data in China

Abstract: Based on provincial panel data of China from 2011 to 2019, this paper discusses the influence and mechanism of the platform economy on the high-quality development of regional economies. It is found that the platform economy has an inverted U-shaped impact on the high-quality development of regional economies. On the left side of the inverted U-shaped inflection point, the platform economy plays a significant role in promoting high-quality economic development; on the right side of the inflection point, the pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 33 publications
1
27
0
Order By: Relevance
“…In other words, the initial stage of the development of the digital economy helps to promote the development of regional low-carbon transformation; when the level of the digital economy is too high, it may restrain regional low-carbon, inclusive growth. This conclusion is consistent with existing research conclusions [51]. According to the calculation, the threshold of the digital economy is 0.3081.…”
Section: Benchmark Regressionsupporting
confidence: 92%
See 4 more Smart Citations
“…In other words, the initial stage of the development of the digital economy helps to promote the development of regional low-carbon transformation; when the level of the digital economy is too high, it may restrain regional low-carbon, inclusive growth. This conclusion is consistent with existing research conclusions [51]. According to the calculation, the threshold of the digital economy is 0.3081.…”
Section: Benchmark Regressionsupporting
confidence: 92%
“…On the other hand, the digital economy has a negative impact on carbon emission reduction. Some scholars have found that some digital platforms use digital technology to form monopolies, which are not conducive to the sustainable development of the regional economy [50][51][52][53][54]. Therefore, digital technology may lead to market monopolies and market failure, hindering the free flow of resources, which is not conducive to green technology innovation and industrial upgrading.…”
Section: Digital Economy and Low-carbon Inclusive Growthmentioning
confidence: 99%
See 3 more Smart Citations